AN INTROSPECTIVE APPROACH TO WOMEN’S INTERCULTURAL FIELDWORK. FEMALE RESEARCHER’S NARRATIONS BASED ON THEIR INTERCULTURAL EXPERIENCES FROM THE FIELD - Kurcińska, Lidia (Society Register, 2017)
Recenzja książki autorstwa Urszuli Markowskiej-Manisty i Justyny Pilarskiej An Introspective Approach to Women`s Intercultural Fieldwork. Female researcher`s narrations based on their intercultural experiences from the field. Warszawa: Wydawnictwo Akademii Pedagogiki Specjalnej, ss. 188.